Short Communication: Zooplankton as indicator of trophic status of lakes in Ilmen State Reserve, Russia - Irina V. Mashkova; Anastasiya Kostryukova; Elena Shchelkanova; Viktor Trofimenko (Society for Indonesian Biodiversity, 2021)
Abstract. Mashkova IV, Kostryukova AM, Shchelkanova EE, Trofimenko VV. 2021. Short Communication: Zooplankton as indicator of trophic status of lakes in Ilmen State Reserve, Russia. Biodiversitas 22: 1448-1455. Zooplankton is a potentially powerful tool for assessing the trophic state of aquatic ecosystems. The current paper studied taxonomic composition and biomass of zooplankton communities in ten lakes within Ilmen State Reserve, Chelyabinsk region, Russia and identified the influence of trophic status on its formation. Integrated samples were taken from epilimnion in the summer of 2016-2019. Several criteria were used to determine trophic status: the taxonomic structure and biomass of zooplankton; some hydroecological indicators some hydroecological indicators and the Carlson index. The trophic status of the studied lakes, determined based on the zooplankton biomass, revealed that most of the lakes were in the status of mesotrophic. The number of zooplankton species in the lakes was 44 with Pleuroxus laevis, Bosmina longirostris, Simocephalus vetulus were the most numerous species in mesotrophic lakes; while Chaetonotus ploenensis, Keratella quadrata frenzeli, Leptodora kindti are rare. Zooplankton communities of Bolshoye Miassovo and Maloye Miassovo Lakes were characterized by high species diversity and considered as one of the most significant among the foothill lakes of the eastern slope of South Ural. The study reveals that hydroecological assessment of the ecological status is not exactly precise, as values are not stable and can change not only under the anthropogenic influence but also due to many natural abiotic environmental factors. The research shows that species composition and biomass of zooplankton communities could provide a more accurate assessment of the trophic status of water-bodies.